2016
DOI: 10.1007/s12008-016-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of direct solar radiation for cost-effectiveness analysis of V-Trough photovoltaic devices

Abstract: In the urge to make solar energy competitive enough to directly face fossil fuels, several approaches result crucial for their intended capacity to maximise the energy that can be produced with a given photovoltaic area. Low Concentration Photovoltaics (LCPV) and tracking methods can be integrated in V-Trough solar devices to increase their effective solar harvesting area through low-cost non-imaging optics. As a tool to support the design and simulation of such devices, this work proposes an analytical and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Depending on the given performance priorities, any of these indicators and indices can be established as the fitness function to be optimized by a genetic algorithm. These indicators and indices are an extension of the V-Trough modeling framework proposed by Arias-Rosales and Mejía-Gutiérrez [24]. Therefore, they are dependent on the same assumptions, namely, the optical performance is solely based on the solar beam radiation interactions and no temperature losses are considered.…”
Section: Description Of the Applied Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the given performance priorities, any of these indicators and indices can be established as the fitness function to be optimized by a genetic algorithm. These indicators and indices are an extension of the V-Trough modeling framework proposed by Arias-Rosales and Mejía-Gutiérrez [24]. Therefore, they are dependent on the same assumptions, namely, the optical performance is solely based on the solar beam radiation interactions and no temperature losses are considered.…”
Section: Description Of the Applied Problemmentioning
confidence: 99%
“…Personalized V-Trough set-ups can be interactively explored and evaluated with "VTDesign", a generative software developed by Arias-Rosales and Mejía-Gutiérrez [23]. VTDesign is based on a computationally-inexpensive, yet flexible, geometrical and analytical model [24]. This model can be used to simulate the interactions between the V-Trough's elements and the solar beam radiation, which is typically taken as 90% of the global radiation on average [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low concentration systems are attractive to small scale applications as the potential increase in temperature has a small effect on the performance of the cell [15]. For this reason, VT devices with a concentration ratio ( ) below a value of 3 result in a significant cost-benefit rate for these systems [16]. Many of the models for PV and CPV systems use ray tracing methods, based on geometric optics [17] and comprise a wide variety of tools for the modelling of CPV systems [18] such as VTDesign® which is used here.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there has been some success in estimating direct radiation worldwide using various methods. For example, Bertrand [36] evaluated decomposition models of varying degrees of complexity to estimate direct solar irradiance from Meteosat second generation images over Belgium; Rosales [37] proposed an analytical and numerical model to simulate the interactions of direct solar radiation. Gueymard [38,39] compared four models (CPCR2, MLWT2, REST and Yang) and concluded that the newly developed MLWT2 model provides the best performance in all direct solar radiation estimation tests.…”
Section: Introductionmentioning
confidence: 99%